Primary students’ satisfaction with CLIL and perceived CLIL linguistic difficulty. - Barrios-Espinosa, María Elvira; Acosta-Manzano, Irene; Acosta-Manzano, Irene (Taylor & Francis, 2020)
This study investigated primary students’ perceptions of Content and Language Integrated Learning (CLIL) Natural Science and Social Sciences and variations in perceptions by individual and social factors. The sample comprised 524 Spanish-speaking students aged 9–13 years from bilingual Spanish-English schools in Andalusia (Spain). The study obtained two measures, namely one of satisfaction with CLIL and one of perception of CLIL linguistic difficulty, and investigated the relationships between them and with individual and social factors. The findings indicate that, on average, the participants’ satisfaction with CLIL is relatively high and that they do not find it particularly challenging from a linguistic point of view. However, around 20% of the participants experienced mild to severe difficulty regarding the language of instruction. A moderate to strong relationship was found between CLIL satisfaction and linguistic difficulty, and these were both statistically associated with mother's level of education, availability of help with homework at home, and relatives’ use of English at work. These findings suggest that socioeconomic status factors are associated with primary students’ perceptions of CLIL and may underlie their success and continuation in CLIL secondary education. It is argued that investment in language support is needed for the most disadvantaged students.
Keywords: Enseñanza primaria; Enseñanza bilingüe; Content and Language Integrated Learning; SES factors; Bilingual programme; Students’ perceptions; Students’ satisfaction; Linguistic difficulty; Primary education